PERSEPSI, EKSPEKTASI DAN KEPUASAN ORANG TUA TERHADAP PENDIDIKAN AGAMA ISLAM ERA PEMBELAJARAN TATAP MUKA TERBATAS DI SDIT ANIC BANJARBARU - Norjannah Norjannah (PROCEEDING UMSURABAYA, 2022)
This study aims to determine the perceptions, expectations and satisfaction of parents on Islamic religious education in the era of Limited Face-to-face Learning at SDIT ANIC Banjarbaru. This study uses a qualitative method with a descriptive approach. The research location is SDIT ANIC Banjarbaru. The subjects in this study were parents, teachers, headmasters and students. The main informants are parents, while the supporting informants are teachers, school principals and students. The results showed that parents' perceptions of the Islamic religious education process in the Limited Face-to-face Learning era were classified as good. The expectations of parents are that schools do not only emphasize the learning process in the cognitive domain, but also in the affective and psychomotor domains, considering that the purpose of Islamic religious education is more emphasized in the affective and psychomotor domains. The satisfaction of parents with the process of Islamic religious education can be said to be satisfied.Â Keyword: Perceptions; Ekspectations; Satisfactions of ParentsÂ